An All-Textile Non-muscular Biomimetic Actuator Based on Electrohydrodynamic Swelling - Uduste, Ilmar; Kaasik, Friedrich; Johanson, Urmas; Aabloo, Alvo; Must, Indrek (Frontiers in Bioengineering and Biotechnology, 2020)
Mass transfer from one part of an organism to another constitutes a fundamental non-muscular movement strategy in living organisms, in particular in plants. The demonstrable simplicity and safety make non-muscular actuators especially attractive for distributed configurations such as in wearable robotic applications on a textile platform. However, practical arrangements for integrating actuators as inherent parts of textiles is an ongoing challenge. Here we demonstrate an electrohydrodynamic ionic actuator that combines two textiles of natural origin. The first textile—viscose-rayon-derived activated carbon cloth—consists of high-surface-area monolithic fibers that provide electrical and mechanical integrity, whereas the other textile—silk—contributes to mechanical integrity in the lateral direction while preventing the conductive textiles from contacting. By injecting an electronic charge into the activated carbon cloth electrodes, the migration of the electrolyte ions is initiated in the porous network in-between the electrodes, causing non-uniform swelling and eventually bending of the laminate. The three-layer laminate composed of integral textile fibers demonstrated a ~0.8-% strain difference. Electrical control over a fluid movement in a textile platform provides a scalable method for functional textiles not limited to actuation.